FUNCTIONING LOCAL CULTURE IN EFL READINGS - Utami Kusuma Ningtyas; Chuzaimah D. Diem; Machdalena Vianty (Sriwijaya University Learning and Education International Conference, 2016)
Curriculum has mandated that communicative competence is the main objective of teaching English in Indonesia. Therefore, target culture is embedded with language in classroom. Globalization, in other hand, has imposed teachers to reconsider the inclusion of local culture. Reading material is one of the medium to promote local culture. This paper elaborates schemata theory and cultural aspects included in reading materials utilized by students.